2023
DOI: 10.1371/journal.pone.0293600
|View full text |Cite
|
Sign up to set email alerts
|

Persistent symptoms are associated with long term effects of COVID-19 among children and young people: Results from a systematic review and meta-analysis of controlled studies

Sanaz Behnood,
Fiona Newlands,
Lauren O’Mahoney
et al.

Abstract: Background Research on the long-term impact on COVID-19 in children and young people (CYP) has been published at pace. We aimed to update and refine an earlier systematic review and meta-analysis to assess the current evidence for Post-COVID-19 Condition in CYP. Methods Studies from the previous systematic review were combined with studies from a systematic search from July 2021 to November 2022 (registration PROSPERO CRD42021233153). Eligible studies included CYP aged ≤19 years with confirmed or probable SA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Systematic reviews have identified over two-hundred symptoms associated with PCC in CYP, including headaches, shortness of breath, fatigue and cough 4 , 5 . However, research into the long-term impact of SARS-CoV-2 has been challenging for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Systematic reviews have identified over two-hundred symptoms associated with PCC in CYP, including headaches, shortness of breath, fatigue and cough 4 , 5 . However, research into the long-term impact of SARS-CoV-2 has been challenging for a number of reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Current prevalence estimates of Long COVID in young people vary greatly, ranging from 1-70% ( Asadi-Pooya et al, 2021 ; Hahn et al, 2023 ; Pellegrino et al, 2022 ), in part reflecting the diagnostic challenges associated with the condition. Systematic reviews and meta-analyses on the prevalence of these enduring symptoms suggest the condition is complex with multisystemic symptoms including fatigue, headaches, brain fog, post exertional malaise and shortness of breath ( Behnood et al, 2022 , 2023 ; Jiang et al, 2023 ; Lopez-Leon et al, 2022 ). However, the trajectory of the condition is not clear as symptoms fluctuate and may relapse over time ( Ziauddeen et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%